EFEKTIFITAS MODEL PEMBELAJARAN KOOPERATIF TIPE FORMULATE SHARE LISTEN CREATE (FSLC) PADA PEMAHAMAN KONSEP SISWA - Atika Defitasari (Departemen Matematika, 2018)
Abstract Under standing of mathematical concept is basic ability that students have to posses,but in fact understanding of mathematical concept in SMPN 2 Padang grade VII is still low, it needs to be improved. In learning, teachers incline use teacher center learning. One attempt to overcome this problem is applied a learning model that can facilitate students to understanding the material and build their own knowledge. Learning model that can be applied is Cooperative Learning type Formulate Share Listen Create (FSLC). Type of the research is quasi experiment with Static Group Design. The purpose of this research is to describe the impact of this model for understanding of mathematical concept. Based on data analysis by using t test P-value = 0,019< ???? = 0,05, it can be conclude that under standing of mathematical concepts of students which study with cooperative type FSLC is better than conventional learning. Keywords—cooperative learning, formulate share listen create, comprehension of mathematical concept, conventional learning.